ESSENTIAL HYPERTENSION ORIGIN, CAUSES AND PREVENTION - Baxrillayev Yusufxon; Komilova Moxinur; Salimova Malika; Murodullayeva Moxinur (Journal of Science in Medicine and Life, 2024)
Many people suffer from hypertension. Medical professionals diagnose "arterial hypertension" in a person whose blood pressure is stable at 140/90 mm Hg. The word "primary" means that there are no pathologies yet, i.e. Blood pressure does not rise due to any serious illness.